Conceptions of parents of adolescent students about the sexuality of their children - Pollyanna de Siqueira Queirós; Laurena Moreira Pires; Marcos André Matos; Ana Luiza Neto Junqueira; Marcelo Medeiros; Márcia Maria de Souza (Universidade Federal do Ceará, 2016)
Objective: to know the conceptions of parents of adolescent students about the sexuality of their children. Methods: it is a qualitative research modality Strategic Research, using focus groups guided by a semi structured instrument with 15 parents of adolescent students. The data were analyzed by content analysis in which the following categories emerged: "Understanding aspects related to sexuality"; "Difficulties for dialogue"; "Facilities for dialogue"; and "The tasks of the family and the school to support the theme." Results: parents had superficial knowledge and misconceptions on the subject. Great difficulty of dialogue between parents and children has been identified, justified by ignorance and timidity of parents and the lack of opening of the adolescent, still, there was recognition of family responsibility in this context. Conclusion: there is need for expansion of intersectoral work involving segments of the education, health and universities to support families with information about sexuality in the school context.